Soil carbon plays a role in the climate impact of diet and its mitigation: the Finnish case - Saarinen, Merja; Heikkinen, Jaakko; Ketoja, Elise; Kyttä, Venla; Hartikainen, Hanna; Silvennoinen, Kirsi; Valsta, Liisa; Lång, Kristiina (Frontiers in Sustainable Food Systems, 2023)
Diet has a significant impact on the consumer’s climate impact, and a radical global change in the food system is necessary. However, the change needs to be interpreted and adapted to local conditions. To support national climate policy, we evaluated current Finnish diet and its four alternatives: “current diet”; “meat to half diet”; “meat to a third diet”; “a diet rich in fish and milk”; and “a vegan diet”. We created the FoodMin model to simultaneously address both climate impacts and nutrient uptake and to combine carbon dioxide (CO2) emissions from soil organic matter (SOM) degradation with dietary climate impact assessments. As a well-established assessment method remains lacking, product group-specific estimates for the CO2 emissions of SOM origin were produced in two different ways, based on long-term observational data or by modelling with the Yasso07. We also examined, using three scenarios, how much the achievement of soil carbon (C) balance in Finnish production could affect the climate impact of the diet. The climate impact of the current diet was 6.0 kg CO2 per person per day, and for alternative diets, the change compared with the current diet was -14%, -20%, -31%, and -39% respectively, for “meat to half” (5.2 kg CO2 eq. per person per day), “meat to third” (4.8), “a diet rich in fish and milk” (4.2), and “the vegan diet” (3.7). SOM-derived CO2 emissions from domestic fields accounted for 18% of the climate impact of the current diet and up to 23% of alternative diets. In terms of the soil C-balance scenarios, all actions together could mean a 3–13% reduction in the climate impact of the diet: the more products of animal origin, the more reduction opportunities in the diet. With the change in diet, these measures could reduce the climate impact of diets by 13–41%. The nutritional value of a “diet rich in fish and milk” was the best. The study revealed that SOM-induced CO2 emissions and SOM-related activities play a very important role in the climate impact of the diet and its mitigation; they cannot be ignored in dietary assessments in addition to direct product choices.